Analisis data peminjaman perpustakaan untuk meningkatkan layanan dan efisiensi pengelolaan UPT Perpustakaan UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Ritonga, Ihdi Syahputra (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research was conducted to investigate how data analysts can be used to improve library services for librarians and visitors. In today's digital era, libraries are required to provide better and more efficient services to meet the needs of their users. Data analyst, as a science that utilizes technology to collect, analyze and utilize data, is considered to have great potential for use in libraries. This research was conducted using a quantitative approach. The data obtained from the catalog dataset library were then analyzed using relevant data analysis techniques, the authors conducted a literature review to gain a deeper understanding of how data analysts have been implemented in the library. The results of the analysis of the data, over the past 5 years, the average number of loans that came from alumni was 566 times. The Visit Trend data shows that there has been a gradual increase from the beginning of 2020 to May 2022, February 20th has the most visits with a total of 494 visits, followed by March and May. books with a high number of loans, such as